2020
DOI: 10.1101/2020.09.30.20204693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Randomized Controlled Trials of Early Ambulatory Hydroxychloroquine in the Prevention of COVID-19 Infection, Hospitalization, and Death: Meta-Analysis

Abstract: Objective--To determine if hydroxychloroquine (HCQ) reduces the incidence of new illness, hospitalization or death among outpatients at risk for or infected with SARS-CoV-2 (COVID-19). Design--Systematic review and meta-analysis of randomized clinical trials. Data sources--Search of MEDLINE, EMBASE, PubMed, medRxiv, PROSPERO, and the Cochrane Central Register of Controlled Trials. Also review of reference lists from recent meta-analyses. Study selection--Randomized clinical trials in which participants were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…Despite the evidence against the use of chloroquine or hydroxychloroquine the controversy continues. A meta-analysis that was posted on September 30th 2020 on the medRxiv preprint server concluded that hydroxychloroquine use in outpatients reduced hospital stay and mortality despite none of the five RCTs included in the analysis individually demonstrating benefit (208).…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…Despite the evidence against the use of chloroquine or hydroxychloroquine the controversy continues. A meta-analysis that was posted on September 30th 2020 on the medRxiv preprint server concluded that hydroxychloroquine use in outpatients reduced hospital stay and mortality despite none of the five RCTs included in the analysis individually demonstrating benefit (208).…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
“…To increase power and synthesize the current landscape, a meta-analysis of outpatient randomized controlled studies was conducted, examining prevention of COVID-19 in 2 trials, and reduced hospitalization or death 3 trials. Using a composite endpoint of reduced risk of infection or risk of hospitalization or death, Ladapo et al identified a significant benefit with early use of hydroxychloroquine among outpatients infected with SARS-CoV-2 [36]. Thus, the potential benefit of hydroxychloroquine in the early management of outpatients should be of great interest and the subject of continued rigorous investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Уже c начале пандемии COVID-19 возник интерес к хлорохину и гидроксихлорохину, синтетическим производным хинина (4-аминохинолиновые препараты), которые применяются в медицине более 70 лет -в начале для лечения малярии, а затем и широкого круга ИВРЗ [35] и обладают широким спектром антивоспалительных, иммуномодулирующих и антивирусных эффектов [35,36]. Хотя мета-анализы результатов рандомизированных клинических исследований (как правило, низкого качества) не подтвердили эффективность (снижение летальности) гидроксихлорохина у пациентов с тяжелым COVID-19 [37], имеются данные, что превентивное применение этого препарата у пациентов с легким и средне-тяжелым течением COVID-19 ассоциировалось со снижением риска госпитализации и даже летальности [38].…”
Section: коронавирусная болезнь 2019 (Covid-19) и иммуновоспалительныunclassified